Reflexões sobre o descumprimento as medidas socioeducativas em meio aberto por adolescentes no município de Palmas - TO - França, Marly da Silva (Universidade Federal do Tocantins, 2024)
The objective of this study is to understand the reasons that lead adolescents to disregard socio - educational measures in the municipality of Palmas - TO, among the adolescents linked to the service in the period from January to August of 2016. In this way, We structure the work as follows. In the first moment, we present the transformations that have occurred throughout history in the politics of child and adolescent care, as well as the adolescent who is attributed authorship of an infraction and the issue of noncompliance. In the second moment, we discussed the child and adolescent care network, emphasizing the bodies that have involvement with sentenced adolescents, and socio-educational measures in the municipality of Palmas. In the third moment, we tried to reflect on the noncompliance with socio - educational measures in open environment by adolescents in the municipality of Palmas - TO. To do this, we conducted field research, which was initially done with the documents, to outline the profile of adolescents who failed to comply with the measures, and then focused on the professionals who work with these adolescents. We conducted semi-structured interviews with these students in order to understand the factors that lead adolescents to disregard a socio-educational measure in the open. As a result, we found that among the adolescents who disagree, the majority are male, the age group predominates is 19 years old, they belong to low-income families, most of them live with their mother, and the predominance of the Use of weapons. We also found that the reasons that lead teenagers to disregard socio-educational measures in an open environment are related to the conditions that the Service offers, as well as the specifics of adolescents 'and their families' lives. Keywords: Adolescents. Educational Measures. Noncompliance